2017
DOI: 10.1016/j.ultsonch.2016.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reaction temperature on the size and morphology of scorodite synthesized using ultrasound irradiation

Abstract: Synthesis of scorodite (FeAsO·2HO) using dynamic action agglomeration and the oxidation effect from ultrasound irradiation was investigated. The effect of different reaction temperatures (90, 70, 50, and 30°C) on the size and morphology of scorodite particles synthesized under O gas flow and ultrasound irradiation was explored because the generation of fine bubbles depends on the solution temperature. At 90°C, the size of scorodite particles was non-homogeneous (from fine particles (<1μm) to large particles (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…A Fe/As ratio in the range of 1.0-3.0 is available for the synthesis of scorodite in different conditions by using pure chemical reagents. 32,35,38,46,47,49,62 The inuence of Fe/As ratio on the scorodite synthesis was investigated in the range of 1.0-2.0, as shown in Fig. 8.…”
Section: Effect Of Fe/mentioning
confidence: 99%
See 2 more Smart Citations
“…A Fe/As ratio in the range of 1.0-3.0 is available for the synthesis of scorodite in different conditions by using pure chemical reagents. 32,35,38,46,47,49,62 The inuence of Fe/As ratio on the scorodite synthesis was investigated in the range of 1.0-2.0, as shown in Fig. 8.…”
Section: Effect Of Fe/mentioning
confidence: 99%
“…40 | RSC Adv., 2020, 10, [29][30][31][32][33][34][35][36][37][38][39][40][41][42] This journal is © The Royal Society of Chemistry 2020 into account balances of minimal arsenic loss and maximal removal rate of sulfuric acid, a nal pH of 0.5 is xed in Stage-I. The nontoxic gypsum with an As leaching concentration of 3.36 mg L À1 below the regulatory limit was obtained, resulting in a sulfuric acid removal rate of 80% with a negligible arsenic loss.…”
Section: Neutralization Sludge/t D à1mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous work, we reported that oxidant radicals generated under 200 kHz ultrasound irradiation and O 2 gas flow contribute to the oxidation reaction to synthesize scorodite. 11,12) Thus, when the gas mixture contains more than 50 vol % of CO 2 , the oxidation reaction during the ultrasound agglomeration process is inhibited because of the reduction in O 2 gas and oxidant radicals, which are responsible for oxidation. Therefore, a large proportion of CO 2 gas (≥50 vol %) prevented nuclei formation by oxidation of radicals and O 2 gas during ultrasound irradiation (10 min) at the early reaction stage.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the particle size of scorodite is influenced by its precursor. Larger scorodite is synthesized when the size of the precursor is increased by agglomeration [19][20][21]. Even though the precursor plays a significant role in the growth of scorodite during atmospheric scorodite synthesis, the speciation of the precursor has not been characterized.…”
Section: Introductionmentioning
confidence: 99%